Increasing awareness of post-harvest best practices for maize and bean farmers [Rwanda] - Ingabire, Christine (Technical Centre for Agricultural and Rural Cooperation, 2018)
In Rwanda, the professionalisation of the maize and bean value chains is being given priority by the government. Maize and beans are important income earners for farmers. In order for them to meet the quantity and quality demands of buyers, a project has been designed to increase farmers' awareness of post-harvest best practices.